Characterization of dissertations and theses of a post-graduate program in nursing in Ceará: descriptive-exploratory study - Francisco Stélio Sousa; Rosilene Santos Baptista; Quitéria Clarice Magalhães Carvalho; Thelma Leite de Araujo; Marta Maria Coelho Damasceno (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2009)
Descriptive study, exploratory and quantitative. The aim was to characterize the production of the Nursing Post-Graduate Program at the Federal University of Ceará, through the thesis. The accessibility was used as a criterion for inclusion in the sample, comprising 196 dissertations and 76 thesis presented between 1995 and 2007. The variables were: years of defense, approach, background, sample, the theoretical framework and lines of research, being categorized as defining the area of Nursing / CAPES. Descriptive statistics was used and the analysis was guided by the relevant literature on the subject. The results showed a preference for qualitative approaches, samples of adults, women and nurses in the hospital setting. The benchmarks used were more nursing theories, in addition to phenomenology and Social representations. The research lines that predominated were Procedure of caring and caring in nursing, related to care area. The results can map the knowledge produced, showing strengths, weaknesses and direction in trying to achieve excellence of the program.